THE INFLUENCE OF TAX AGGRESSIVENESS, PROFIT PERFORMANCE AND LEVERAGE ON CORPORATE TRANSPARENCY - Fajar Rina Sejati; Septyana Prasetianingrum (Universitas Airlangga, 2019)
This study aims to analyze the effect of tax aggressiveness (tax aggressiveness), earnings performance, and leverage on corporate transparency. The research method uses secondary data, all of which are taken from the financial statements of companies listed on the Indonesia Stock Exchange for the period 2014 – 2017. The data analysis method used in this study is multiple linear regression analysis. In this study, the data will be processed using SPSS version 25.0 software. The results of this study indicate that tax aggressiveness has no effect on company transparency, earnings performance has no effect on company transparency, leverage has no effect on company transparency, company age has no effect on company transparency, and company size does not affect company transparency. This research shows that the company's transparency is an important thing, it is hoped that every company in running the company ethically maintains company transparency.